STRATEGY FOR INTEGRATING SOCIAL SECURITY PROTECTION INTO SPORTS EVENTS - Jeperson Pardede; Noer Azam Achsani; Hendro Sasongko (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
Background: The participation of informal workers (Bukan Penerima Upah / BPU) in BPJS Ketenagakerjaan remains low despite the rapid growth of sports events in Indonesia. Running events involve various informal actors who face occupational risks, yet most events still rely on liability waivers rather than formal social security protection. Although national regulations mandate protection for sports actors, implementation remains fragmented and non-integrated. Objective: This study aims to analyze the perceptions and preferences of sports event participants and organizers toward social security protection and formulate an integration strategy to increase informal workers’ participation in BPJS Ketenagakerjaan Samarinda. Method: This study employed a mixed-method approach using Structural Equation Modeling–Partial Least Squares (SEM-PLS) and Soft System Methodology (SSM). SEM-PLS was used to analyze the perceptions and preferences of runners and sports event organizers toward social security protection, while SSM was applied to formulate an integration strategy for BPJS Ketenagakerjaan protection within sports events. Conclusion: The SEM-PLS results indicate that perceived behavioral control, particularly ease of registration and process simplicity, is the most influential factor affecting runners’ intention to participate, while product attributes are the dominant factor for event organizers. The SSM analysis further reveals that successful integration requires regulatory support, digital registration integration, bundled participation mechanisms, cross-sector collaboration, and continuous monitoring. Therefore, a system-based and integrated approach is more effective than conventional voluntary approaches in expanding social security coverage within the sports event ecosystem.